Halal Logo Verification-Kiosk - M.Y. Noraihah; I.K. Marlina; M.F. Hamzah (Universiti Sains Islam Malaysia, 2024)
A Halal Logo Verification Device is invented to assist muslim consumers in checking the halal status of any products in the market. The device verifies status of the consumer products based on the database registered with Jabatan Kemajuan Islam Malaysia (JAKIM). Many manufactures manipulate the halal logo for their uncertified products. Some manufactures do not renew the halal certification of their products. At this moment, consumers can only check the halal status of the product through JAKIM portal (www.halal.gov.my) or by sending the barcode products using Short Message Service (SMS), these services are limited and exhausted. A Halal Logo Verification device has an extensive database about the halal status of products in market. The use of Halal Logo Verification Device allows muslim consumers to easily check before purchasing a product and it is invented to be placed at all hypermarkets in Malaysia.